The Brugada Syndrome: A Rare Arrhythmia Disorder with Complex Inheritance - Gourraud, Jean-Baptiste; Barc, Julien; Thollet, Aurélie; Le Scouarnec, Solena; Le Marec, Hervé; Schott, Jean-Jacques; Redon, Richard; Probst, Vincent (Frontiers in Cardiovascular Medicine, 2016)
For the last ten years, applying new sequencing technologies to thousands of whole exomes has revealed the high variability of the human genome. Extreme caution should thus be taken to avoid misinterpretation when associating rare genetic variants to disease susceptibility. The Brugada syndrome (Brs) is a rare inherited arrhythmia disease associated with high risk of sudden cardiac death (SCD) in the young adult. Familial inheritance has long been described as Mendelian, with autosomal dominant mode of transmission and incomplete penetrance. However, all except one of the 23 genes previously associated with the disease have been identified through a candidate gene approach. To date, only rare coding variants in the SCN5A gene have been significantly associated with the syndrome. However, the genotype/phenotype studies conducted in families with SCN5A mutations illustrate the complex mode of inheritance of Brs. This genetic complexity has recently been confirmed by the identification of common polymorphic alleles strongly associated with disease risk. The implication of both rare and common variants in Brs susceptibility implies that one should first define a proper genetic model for Brs predisposition prior to applying molecular diagnosis. Although long remains the way to personalized medicine against Brs, the high phenotype variability encountered in familial forms of the disease may partly find an explanation into this specific genetic architecture.